Troubling Discourses of Poverty in Early Childhood in the UK. (29th July 2019) - Lyndon, Sandra
Abstract : Poverty in early childhood is pervasive, affecting every aspect of children's lives. Under current government policies child poverty in the UK is predicted to rise to 40 per cent by 2022. Dominant discourses of poverty have historically focussed on an over‐arching discourse of moral responsibility, essentially relating to notions of deserving and underserving poor. This paper examines how government policy continues to significantly impact on young children and families on low incomes in early childhood and how stigmatised discourses about welfare, work are pervasive. It is argued that discourses of redistribution and children's rights deserve greater recognition if poverty is to be addressed.